The Role and Place of Speech in the Formation of a Child's Thinking (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Speech plays a very important role in making a person a full-fledged member of society, because the human thinking becomes confused in the process of speech communication. One of the most urgent demands of our time is to educate a well-rounded person, and our state is doing a lot of work in this regard. In "State students for the development of children of preschool age", four types of child personality development are based on: physical, social-emotional, speech, and preparation for reading and writing, which together constitute the integrity of child development.